New larval host records, parasitoid records, and DNA barcoding data for North American leaf-mining leaf beetles (Coleoptera: Chrysomeloidea) - Eiseman, Charles S.; Feldman, Tracy S.; Palmer, Michael W. (Zootaxa, 2024)
We discuss 46 species of North American leaf-mining leaf beetles (Coleoptera: Chrysomelidae, Megalopodidae), plus one external feeder observed to spin its cocoon within the leaf mine of another insect. For each species, we review previous records of larval and adult hosts and associated hymenopteran parasitoids, augmenting these with our own observations, including the first accounts of oviposition and larval habits for many species. We present the first rearing records for 12 of these species: Anisostena californica Van Dyke, A. funesta (Baly), A. lecontii (Baly), A. perspicua (Horn), Microrhopala excavata (Olivier), Odontota floridana Butte, Stenopodius lateralis (Schaeffer), Altica lazulina LeConte, Dibolia obscura Parry, Monoxia inornata Blake, Zeugophora puberula Crotch, and Z. varians Crotch; as well as 18 new state and provincial records for chrysomeloids, although some of these are based on tentative identifications. We also present original DNA barcoding data showing intra- and interspecific variation among 18 species of hispines (Chrysomelidae: Chalepini). Our data do not provide evidence for cryptic species within Baliosus nervosus (Panzer), Sumitrosis inaequalis (Weber), and S. rosea (Weber) hypothesized based on differences in larval hosts and leaf mines. However, they do suggest the possibility of cryptic species within Tilia-feeding B. nervosus, as well as within S. ancoroides (Schaeffer) and perhaps Microrhopala excavata and Odontota horni Smith. Our barcoding data also support the recognition of the Silphium-feeding M. laetula LeConte as distinct from the Solidago-feeding M. vittata (Fabricius).